Spillover effects from multinational enterprises: A literature review - Petr Šmelc (World Economy and Policy (WEP), 2023)
Multinational enterprises play a significant role in the global economy. Their activities can have positive impacts on host countries as these companies tend to bring new capital, technology, and knowledge. Nevertheless, negative effects linked to their presence occur as well. Most studies focus on the overall impact of FDI on economic growth. In this paper, we go beyond this relationship and examine the literature describing specifically the indirect impacts of the activities of multinational corporations on host economies, the so-called spillover effects. We highlight the most relevant studies on this topic. Spillover effects occur both across and within industries and can significantly increase the productivity of domestic companies. The magnitude of these impacts is, however, significantly dependent on the level of development of the host economy and the absorptive capacity of local companies.
Keywords: 330; Economic Growth; Foreign Direct Investment; Global Economy; Multinational entreprises; Spillover Effects